IMPLEMENTASI SUPERVISI KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SMP MUHAMADIYAH 7 PADANG - Azvi Rahmi (Menara Ilmu, 2020)
This study aims to describe the role of the principal in providing supervision to improve teacher performance. This study uses qualitative research with a descriptive approach. Data collection techniques using interviews, observation and documentation.Whereas the data wetness uses triangluation. The results showed that: There are still some teachers who do not make learning tools, such as lesson plans. Supposedly, the implementation of learning (RPP) made is a guide for teachers in implementing learning. There are some teachers who drop out of school before class ends, for example picking up their children after school. There are still some teachers who lack discipline in doing their tasks, which can be seen from the presence of teachers who often arrive late to school and go home early and often leave class during class time explain in detail to students who make students less understand the subject matter. There are still some of the teachers do not use media in the learning process. From some of these problems can be overcome by giving supervision of school principals to teachers to improve teacher performance. The supervision of the principal can be done in various ways. Keywords: Supervision Of The Principal, Teacher Performance